Dosimetry Assessment of Potential Hazard from Visible Light, Especially Blue Light, Emitted by Screen of Devices in Daily Use - Charoenpipatsin N; Yothachai P; Nuntawisuttiwong N; Wongpraparut O; Choosri P; Silpa-archa N (Clinical, Cosmetic and Investigational Dermatology)
Norramon Charoenpipatsin,1 Punyanut Yothachai,1 Nuttaporn Nuntawisuttiwong,1 Ornnicha Wongpraparut,2 Pranomkorn Choosri,3 Narumol Silpa-archa1 1Photodermatology Unit, Department of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand; 2Shrewsbury International School Bangkok, Bangkok, Thailand; 3Department of Biomedical Engineering, College of Health Sciences, Christian University of Thailand, Nakhon Pathom, ThailandCorrespondence: Narumol Silpa-archa, Department of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University, 2 Wanglang Road, Bangkoknoi, Bangkok, 10700, Thailand, Tel +66 2419 4333, Fax +66 2411 5031, Email doctornarumol@gmail.comAbstract: Visible light has been considered to have minimal impact on the skin. However, the increasing use of electronic devices has led to a significant increase in exposure to visible light, especially blue light. We measured the irradiance (mW/cm2) and estimated dose (J/cm2) of visible light and blue light emitted from various electronic devices including smartphones, tablets and computers. The measurement was done in normal screen mode and night shift mode at different brightness levels and distances across six screens. The irradiance and dose of visible light and blue light corresponded to the brightness, distance, and screen size of the devices. This study has shown that the irradiance and dose of visible light and blue light emitted from electronic devices in daily use are small and unlikely to be harmful to human skin.Keywords: visible light, blue light, electronic devices